Posterior Mediastinal Ancient Schwannoma Mimicking a Cyst - Zahra, Kanwal; Khalid, Ahmareen; Ali, Tayyaba; Omair, Maria; Afshan, Gul-; Khursheed, Shaista (International Journal of Pathology, 2018)
Background: Several types of neurogenic tumors can occur in mediastinum and commonly present as posteriormediastinal mass lesions. Generally they are categorized in to those arising from peripheral nerves orsympathetic ganglia. Schwannoma is the most common neurogenic tumor of this area. Generally they arepresented as solid encapsulated lesions and are difficult to miss on radiology. Rarely they can be large enough toundergo cystic degeneration and cause confusion with other cystic mass lesions of the area. Large masses canalso cause pressure symptoms and leads to respiratory compromise.Conclusion: Posterior mediastinal schwannomas though usually are benign and asymptomatic but can provefatal if attain a very large size. It should always be included in the differential diagnosis of posterior mediastinallarge cystic masses. Degenerative nuclear atypia associated with ancient schwannoma should not be confusedwith malignancy. Patient can lead a symptom free life after surgical resection of these tumors.